Design and validation of ultrasound-guided femoral vein puncture robots - LIU Lintao; XIA Jing; CHENG Gan (Jixie chuandong)
ObjectiveFemoral veni puncture is widely used in clinical scenarios such as critical emergency treatment, emergency dialysis, drug rehydration, etc. However, the success rate of femoral veni puncture often depends on the experience of doctors. Thus, an ultrasound-guided robot system for femoral vein puncture was developed.MethodsFirstly, a 2-DOF end puncture actuator of the puncture robot was designed for angle adjustment of the swing arm and femoral vein puncture feeding.Then, based on the 7-DOF serial robot arm, an ultrasound-guided femoral vein puncture robot system was built to ensure the space of ultrasound scanning and puncture. Finally, the positioning accuracy of the end puncture actuator and the robot was verified.ResultsThe test results show that the absolute positioning accuracy of the angle of the puncture swing arm of the end puncture actuator is within 0.5°, the absolute positioning accuracy of the puncture feed is within 0.2 mm, and the spatial repeated positioning accuracy of the needle tip of the femoral vein puncture robot based on the 7-DOF robot arm is within 0.2 mm, meeting the requirements of clinical puncture accuracy. The robot system is built to realize semi-automatic puncture through remote operation, which provides important experience for realizing automatic puncture of femoral veins.